Identification and functional analysis of the geranylgeranyl pyrophosphate synthase gene (crtE) and phytoene synthase gene (crtB) for carotenoid biosynthesis in Euglena gracilis. Issue 1 (December 2016) - Kato, Shota; Takaichi, Shinichi; Ishikawa, Takahiro; Asahina, Masashi; Takahashi, Senji; Shinomura, Tomoko
Abstract Background Euglena gracilis, a unicellular phytoflagellate within Euglenida, has attracted much attention as a potential feedstock for renewable energy production. In outdoor open-pond cultivation for biofuel production, excess direct sunlight can inhibit photosynthesis in this alga and decrease its productivity. Carotenoids play important roles in light harvesting during photosynthesis and offer photoprotection for certain non-photosynthetic and photosynthetic organisms including cyanobacteria, algae, and higher plants. Although, Euglenida contains β-carotene and xanthophylls (such as zeaxanthin, diatoxanthin, diadinoxanthin and 9′-cis neoxanthin), the pathway of carotenoid biosynthesis has not been elucidated. Results To clarify the carotenoid biosynthetic pathway inE. gracilis, we searched for the putativeE. gracilis geranylgeranyl pyrophosphate (GGPP) synthase gene (crtE ) and phytoene synthase gene (crtB ) by tblastn searches from RNA-seq data and obtained their cDNAs. Complementation experiments inEscherichia coli with carotenoid biosynthetic genes ofPantoea ananatis showed thatE. gracilis crtE (EgcrtE ) andEgcrtB cDNAs encode GGPP synthase and phytoene synthase, respectively. Phylogenetic analyses indicated that the predicted proteins ofEgcrtE andEgcrtB belong to a clade distinct from a group of GGPP synthase and phytoene synthase proteins, respectively, of algae and higher plants. In addition, we investigated the effects of light stress on the expression ofcrtE andcrtB inE. gracilis. Continuous illumination at 460 or 920 μmol m−2 s−1 at 25 °C decreased theE. gracilis cell concentration by 28–40 % and 13–91 %, respectively, relative to the control light intensity (55 μmol m−2 s−1 ). When grown under continuous light at 920 μmol m−2 s−1, the algal cells turned reddish-orange and showed a 1.3-fold increase in thecrtB expression. In contrast, EgcrtE expression was not significantly affected by the light-stress treatments examined. Conclusions We identified genes encoding CrtE and CrtB inE. gracilis and found that their protein products catalyze the early steps of carotenoid biosynthesis. Further, we found that the response of the carotenoid biosynthetic pathway to light stress inE. gracilis is controlled, at least in part, by the level ofcrtB transcription. This is the first functional analysis ofcrtE andcrtB inEuglena .